Selected glaucoma risk factors and their role in disease progression. Part I – systemic, local and mechanical factors - Kośny, Joanna; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
The aim of this article is to summarise recent knowledge regarding selected glaucoma risk factors and to provide a brief description of the possible interaction mechanism. The article mostly refers to the most common disease variant – primary open angle glaucoma and focuses on systemic factors as well those altering local condition and mechanical properties of involved structures.